2023
DOI: 10.1002/joc.8009
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal characteristics of human thermal comfort across southern Africa: An analysis of the Universal Thermal Climate Index for 1971–2021

Abstract: The 6th Assessment of the Intergovernmental Panel on Climate Change projects increasing thermal-associated morbidity and mortality under anthropogenically induced warming. Over 100 indices exist to quantify thermal stress, and among these, the Universal Thermal Climate Index (UTCI) was developed for regional investigations of thermal stress influences on human health. Although by definition a universal index, current applications are mainly limited to Europe. For regions such as Africa, use of the UTCI has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 97 publications
0
1
0
Order By: Relevance
“…In Africa, Sarah found a wide range of thermal stress experienced, ranging from very strong cold stress to extreme heat stress in southern Africa. The study also noted a significant increase in UTCI with a rate of 0.28 • C decade −1 [27]. Similarly, research by Mohammed in North Africa and the Middle East found UTCI values ranging from 0 • C to 32 • C, with an increasing trend of 0.1 • C to 0.7 • C decade −1 [28].…”
Section: Introductionsupporting
confidence: 66%
“…In Africa, Sarah found a wide range of thermal stress experienced, ranging from very strong cold stress to extreme heat stress in southern Africa. The study also noted a significant increase in UTCI with a rate of 0.28 • C decade −1 [27]. Similarly, research by Mohammed in North Africa and the Middle East found UTCI values ranging from 0 • C to 32 • C, with an increasing trend of 0.1 • C to 0.7 • C decade −1 [28].…”
Section: Introductionsupporting
confidence: 66%
“…In recent years, it has been used by among others Di Napoli et al (2018) for selected European countries, Nemeth (2011) in Hungary, Pecelj et al (2021) in Serbia, Nastos and Matzarakis (2012) in Greece, Urban and Kyselý (2014) in Czechia and Burkart et al (2016) in Portugal. Outside Europe, UTCI has been applied among others in Brazil , India (Dash et al 2017), Japan (Ohashi et al 2018) and China (Ge et al 2016), as well as Iran (Baghideh et al 2016, Roshan et al 2018), South Africa (Roffe et al 2023) and China (Lin et al 2022).…”
Section: Utci [°C] Stress Categorymentioning
confidence: 99%
“…Over the past century, more than 100 indices have been developed and used to assess bioclimatic conditions for human beings [25]. For example, according to the universal thermal climate index (UTCI) used in Europe, there is no heat stress for humans in the range between +9 • C and +26 • C, moderate heat stress ranges from +26 • C to +32 • C, and strong heat stress ranges from +32 • C to +38 • C [26]. The effective temperature index was established to provide a method of determining the relative effects of air temperature and humidity on comfort [25].…”
Section: Introductionmentioning
confidence: 99%